Radiation therapist health literacy training: A qualitative study exploring perceived barriers and attitudes. Issue 4 (November 2020) - Kelly, T.; Arnold, B.; Surjan, Y.; Rinks, M.; Warren-Forward, H.
Abstract: Introduction: Health literacy (HL) is a universal issue in healthcare. While difficult to assess an individual's HL status, the onus is on the health provider to empower patients to seek understanding of health information provided to them. Universal HL training techniques include implementing plain language and the teach-back method. The research aims to explore the perceptions of Australian radiation therapists (RTTs) learning and implementation of these tools with patients. Methods: RTTs attended two communication and HL workshops one week apart. Participants completed three anonymous surveys (before the first workshop, immediately after the second and three months post workshops) and a workshop evaluation was administered after the second workshop. Participants had the opportunity to provide written comments on all surveys and the evaluation form. A thematic analysis was performed on the written comments by two independent researchers. Results: Five themes were revealed after the thematic analysis of the surveys. These themes were: improved patient understanding, impact on professional credibility, practice and timing of using methods, appearing to be condescending to educated patients and increased patient anxiety. The workshop evaluation assessment indicated the success of and improvement for future workshops and revealed seven themes. These were: learning from others, providing a safe environment to share experiences, to be open to learning new methods, more time for learning, role-play aversion, group sizing and thinking beyond the workshops. Conclusion: While strong evidence of using HL tools for improved patient understanding exists, this qualitative review revealed unexpected barriers with implementing both the plain language and teach-back method. Implications for practice: Barriers revealed during HL training could have patient flow on effects when checking for understanding. These challenges need further exploration, to inform all health professionals.